Nasal Lobular Capillary Hemangioma as a Complication after an Endoscopic Transsphenoidal Gonadotrophin-Producing Pituitary Adenoma Resection - Forte, Dalila; Irañeta, Amets Sagarribay; Nabais, Anabela; Figueiredo, António; Mafra, Manuela; Gonçalves, Victor (Journal of Neurological Surgery Reports, 2017)
Background Lobular capillary hemangioma is a rare benign tumor, most frequently located in the head or neck region, the nasal cavity being uncommonly affected. Its etiopathogenesis is not fully established, although traumatic and hormonal factors have been implied.Case Description A 50-year-old female patient underwent an uneventful endoscopic transsphenoidal removal of a pituitary cystic macroadenoma at our institution. Nasal packing was used in postoperative hemostasis. Histopathology was compatible with a gonadotrophin-producing adenoma. One month after the surgery, the patient presented with frequent episodes of epistaxis and a progressively growing nasal mass, which was removed endoscopically. Its pathological examination confirmed a lobular capillary hemangioma.Conclusions The authors present a clinical case combining two possible predisposing factors to the development of a nasal lobular capillary hemangioma: local traumatic injury through surgery and postoperative nasal packing and hormonal influence. This lesion is a rare complication of endoscopic transsphenoidal resections of pituitary adenomas.
Keywords: lobular capillary hemangioma; pyogenic granuloma; endoscopic transsphenoidal pituitary surgery